Strategi Pengembangan Usaha Melalui Analisis Strength Weakness Opportunity Threat (SWOT) dan Identifikasi Kebutuhan Konsumen Pada Usaha Produksi Sepatu - Esron David Sinaga; Derlini Derlini (Fakultas Teknik Universitas Samudra, 2017)
Ud.Kellan Shoes be on strategy SO (aggressive), that is strategy to use the power that is owned to take advantage of the opportunities that exist, this is obtained based on the result of data processing using swot analysis shows that the business development strategy . Then the right strategy to apply to Ud.Kellan Shoes is creativity in making the model improved so that the more diverse forms and models, utilize market potential in fostering good relationships with customers, and collaborating with the government in facilitating new distribution channels. Based on the results of the identification of consumer needs of shoe products Ud.Kellan Shoes then attribute-atributes desired by consumers in business development Ud.Kellan Shoes is the price, of quality, models, and colors.